Pelaksanaan Tindak Penggembalaan bagi Pelayan Khusus Gereja Protestan Maluku Ditinjau dari Perspektif Konseling Pastoral - Ruimassa, Aleta Apriliana; Parera, Lidya (KAMBOTI: Jurnal Sosial dan Humaniora, 2023)
The aim of this study is to provide a comprehensive understanding of the implementation of pastoral care for special servants whose family members commit immoral acts from a pastoral counseling perspective. This study uses library research methods. The literature used is literature that supports writing, namely church regulations in the Maluku Protestant Church (GPM); books related to pastoral care and pastoral counseling, as well as other sources. The author attempts to describe thoughts about how organic regulations regarding special grazing in GPM should be implemented from a pastoral counseling perspective. The findings in this study are that the act of shepherding, which is a form of church discipline in GPM, has indeed been well formulated in the GPM Basic Regulations on Shepherding. Implementation of these pastoral actions is generally carried out in the form of conversations or pastoral counseling. However, as an effort to guide, it seems that the process of pastoral conversations between servants and problematic family members is often only carried out in one go and is limited to providing advice. For servants who have problems, the problems they face are more complex so that pastoral conversations cannot be done just once and in the form of giving advice, but can be more than that. This study concludes that empathy and a willingness to listen are attitudes that pastoral counselors must have so that the act of pastoral care is not interpreted as a punishment. These two attitudes are based on the love of God in Jesus Christ who was present in the world to heal, guide and reconcile when humans fell and were far from God.